IMPACT OF DIGITAL TECHNOLOGY ADOPTION ON PROFITABILITY AND BUSINESS EXPANSION IN SMES (Journal of the Management Sciences, 2025)
The study examined the impact of digital technology adoption on profitability and business expansion in Small and Medium Enterprises (SMEs). Descriptive survey research design was employed and questionnaire was used as the research instrument. The study population comprised 8,395 SMEs operating in Lagos State and Krejcie and Morgan (1970) was used to determine a sample size of three hundred and sixty-seven (367) respondents while purposive sampling technique was used to select the SMEs. Simple percentage was used to analyze the responses of the questionnaire while regression statistics was used to test the hypotheses. Findings revealed that e-commerce integration has significant impact on the revenue growth in SMEs (p < 0.05), digital marketing also has a significant impact on the return on investment (ROI) in SMEs (p < 0.05), automation tools significantly impact the cost efficiency in SMEs (p < 0.05) and customer relationship management (CRM) systems significantly impact the customer retention rate in SMEs (p < 0.05). These findings emphasized that the strategic adoption of digital technologies is no longer optional but essential for SMEs seeking sustainable growth in an increasingly digital economy. It therefore recommended that SME owners and managers should prioritize the integration of digital technologies into their business operations and invest in digital literacy training for themselves and their employees to ensure effective implementation and utilization of these technologies.
Keywords: Business Expansion; Digital Technology; Profitability; E-Commerce Integration; Digital Marketing; Automation Tools; Customer Relationship Management